Analysis of Changes in Criminal Threats in Regulations on Environmental Protection and Management - Arimurti, Danang Johar; Najicha, Fatma Ulfatun (Universitas Negeri Semarang, 2023)
Currently, Indonesia is grappling with serious environmental issues exacerbated by a lack of public awareness and law enforcement. Law enforcement is crucial in addressing environmental problems, necessitating the use of coercive legal instruments such as criminal sanctions. The primary legal framework governing environmental protection and management in Indonesia is Law Number 32 of 2009 concerning Environmental Protection and Management and several amendments to Law Number 6 of 2023 concerning the Ratification of Government Regulation Number 2 of 2022 concerning Job Creation. This article focuses on the changes in criminal sanctions and how these changes occurred by comparing the two aforementioned laws and analyzing them. The results indicate that five articles concerning criminal sanctions have been amended or repealed. This is because four out of the five articles have been simplified for administrative purposes and to avoid legal ambiguities, while one of the five articles cannot be determined due to changes resulting in legal nullity.